2014
DOI: 10.1186/1471-2407-14-118
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular coexpression of CXC- and CC– chemokine receptors and their ligands in human melanoma cell lines and dynamic variations after xenotransplantation

Abstract: BackgroundChemokines have been implicated in tumor progression and metastasis. In melanoma, chemokine receptors have been implicated in organ selective metastasis by regulating processes such as chemoattraction, adhesion and survival.MethodsIn this study we have analyzed, using flow cytometry, the systems formed by the chemokine receptors CXCR3, CXCR4, CXCR7, CCR7 and CCR10 and their ligands in thirteen human melanoma cell lines (five established from primary tumors and eight established from metastasis from d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 50 publications
1
13
0
Order By: Relevance
“…Furthermore, coexpression of ligands and chemokine receptors in neoplastic cells and extracellular matrix suggests that autocrine and paracrine stimulation by the tumor cells results in production of angiogenic factors in response to hypoxia during the first stages of tumor growth, as has been reported in other neoplastic and non-neoplastic conditions [13,[20][21][22].…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Furthermore, coexpression of ligands and chemokine receptors in neoplastic cells and extracellular matrix suggests that autocrine and paracrine stimulation by the tumor cells results in production of angiogenic factors in response to hypoxia during the first stages of tumor growth, as has been reported in other neoplastic and non-neoplastic conditions [13,[20][21][22].…”
Section: Discussionmentioning
confidence: 76%
“…Animal models have been used widely in the study of tumor angiogenesis [11][12][13]. Our aims were to characterization neovascularization of xenotransplanted Os in a nude mouse model at histological, immunohistochemical, ultrastructural, and molecular level, and to consider the use of this model in testing efficacy of new anti-angiogenic drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that melanoma cell lines co-express high levels of chemokine factor receptors and ligands ( 24 ). Chemokines and tumor cell surface receptors are involved in post-melanoma angiogenesis, tumor cell growth, invasion and metastasis of malignant processes ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has become clear that tumour angiogenesis is the result of an imbalance between proangiogenic and antiangiogenic factors, the threshold of change in favour of proangiogenesis is considered to be the angiogenic switch. Several angiogenic factors and chemokines related with angiogenic mechanisms have been studied in different tumour types [6, 8, 9]. We recently communicated these findings in a nude mice osteosarcoma model [10] as well as in two high-grade chondrosarcomas (in press) [11].…”
Section: Introductionmentioning
confidence: 99%